(untitled) (Religious dialogue and cooperation, 2024)
The paper wishes to analyse the religious buildings, with special attention to the Christian ones, considering their transformation due to liturgical and religious reasons. The aim of the research relates to the needs of restoration and conservation of the buildings. The restoration and conservation work compels the understanding of all the historical construction phases of the building itself, and the reasons for them, in order to plan a good project, able to respect their real “authenticity”, according to the Nara charter, established by ICOMOS (International Council of Monuments and Sites) in 1994. The Nara document is inspired by the Venice Charter, approved in 1964 and adopted by ICOMOS in 1965, where, in chapter 3, is stated that: “The intention in conserving and restoring monuments is to safeguard them no less as works of art than as historical evidence.” Restoration refers to the conservation of the historical evidence plus the historical meaning of the building. The traces, even if hidden, of the past, related to different conceiving of the building, must be transferred to the future and made available and comprehensible for everyone. The valorisation of the building, as it is defined by the Italian law of 2004 is a tool for the dissemination of culture, because the culture must be accessible to everyone. The religion and the places devoted to sharing spiritual values, in any geographical and political position and at any time, focusing on intercultural dialogue in a peaceful environment, must be accepted and the work of restoration must be connected with the transformation in order to ensure the respect of the cultural values of religious places. Starting from the re-transformation of Hagia Sophia in Istanbul, from Museum to Mosque and the reception of the transformation from the history and history of art international environment, the paper has the intention to offer an overview, through different examples related to diverse times and places, of the role of the religion and liturgy in the transformation of the house of god and the connection with the cultural environment considering that the transformation has a strong connection with the restoration activities both on the decorative elements and spatial dimension of the religious buildings and their environment.